A Method to Culture GABAergic Interneurons Derived from the Medial Ganglionic Eminence - Franchi, Sira A.; Macco, Romina; Astro, Veronica; Tonoli, Diletta; Savino, Elisa; Valtorta, Flavia; Sala, Kristyna; Botta, Martina; de Curtis, Ivan (Frontiers in Cellular Neuroscience, 2018)
Understanding the mechanisms guiding interneuron development is a central aspect of the current research on cortical/hippocampal interneurons, which is highly relevant to brain function and pathology. In this methodological study we have addressed the setup of protocols for the reproducible culture of dissociated cells from murine medial ganglionic eminences (MGEs), to provide a culture system for the analysis of interneurons in vitro. This study includes the detailed protocols for the preparation of the dissociated cells, and for their culture on optimal substrates for cell migration or differentiation. These cultures enriched in interneurons may allow the investigation of the migratory behaviour of interneuron precursors and their differentiation in vitro, up to the formation of morphologically identifiable GABAergic synapses. Live imaging of MGE–derived cells plated on proper substrates shows that they are useful to study the migratory behavior of the precursors, as well as the behavior of growth cones during the development of neurites. Most MGE-derived precursors develop into polarized GABAergic interneurons as determined by axonal, dendritic and GABAergic markers. We present also a comparison of cells from WT and mutant mice as a proof of principle for the use of these cultures for the analysis of the migration and differentiation of GABAergic cells with different genetic backgrounds. The culture enriched in interneurons described here represent a useful experimental system to examine in a relatively easy and fast way the morpho-functional properties of these cells under physiological or pathological conditions, providing a powerful tool to complement the studies in vivo.